The role of supply chain management in HOL (Hire of labor) process and its challenges of Chevron Bangladesh - Ferdous, Md. Nayeem (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.